Unveiling chemical and biological profiles of plant-fermented kombucha culture through metabolomic studies using LCMS data assisted by MS databases - Costa, Geovanna de Oliveira (2024)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Ciências Físicas e Matemáticas, Programa de Pós-Graduação em Química, Florianópolis, 2024.